(3CNHGQ GdMceGA GdeJbOejf hCNHGQges ((3GHf NdcGf s)
(3ChdgG (B:s
(3hHYO abO SGdfi ef hLHJ NOeJg Ydi hhUdJ eRjJg Edi Gf GLeY dg eNJUQG eajOG s
(3BNQgG (B:s
(3abGd GdTjN HUhJ LhgQi (B: (3dG Edg EdG Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B55 - (3U(B85s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B7 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdJGQjNs